Extracellular Vesicles of Probiotics: Shedding Light on the Biological Activity and Future Applications - Paweł Krzyżek; Beatrice Marinacci; Irene Vitale; Rossella Grande (MDPI AG, 2023)
For many decades, the proper functioning of the human body has become a leading scientific topic. In the course of numerous experiments, a striking impact of probiotics on the human body has been documented, including maintaining the physiological balance of endogenous microorganisms, regulating the functioning of the immune system, enhancing the digestive properties of the host, and preventing or alleviating the course of many diseases. Recent research, especially from the last decade, shows that this health-benefiting activity of probiotics is largely conditioned by the production of extracellular vesicles. Although the importance of extracellular vesicles in the virulence of many live-threatening pathogens is widely described in the literature, much less is known with respect to the health-promoting effect of extracellular vesicles secreted by non-pathogenic microorganisms, including probiotics. Based on this, in the current review article, we decided to collect the latest literature data on the health-inducing properties of extracellular vesicles secreted by probiotics. The characteristics of probiotics' extracellular vesicles will be extended by the description of their physicochemical properties and the proteome in connection with the biological activities exhibited by these structures.